ACC/AHA CLOPIDOGREL CLINICAL ALERT. WHAT MUST BE MODERN ANTIPLATELET THERAPY? - S. J. Martsevich (Столичная издательская компания, 2016)
The ACC/AHA clopidogrel clinical alert about the possibility of ineffective treatment with clopidogrel is discussed. The reason of this resistance to clopidogrel therapy and possible ways to overcome it is considered.